Bayesian latent class analysis of ELISA and RT‐rPCR diagnostic accuracy for subclinical Renibacterium salmoninarum infection in Atlantic salmon (Salmo salar) broodstock. Issue 2 (14th December 2018) - Laurin, Emilie; Morrison, Diane; Gardner, Ian A.; Siah, Ahmed; Powell, James F. F.; Kamaitis, Mykolas
Abstract: Renibacterium salmoninarum infection causes bacterial kidney disease (BKD) in salmonid freshwater and saltwater life stages, with potentially severe financial loss for the aquaculture industry. Preventing vertical transmission, from infected broodstock to eggs, is key to disease management. As there is no perfect reference standard for detecting R. salmoninarum, we used Bayesian latent class analyses to compare real‐time reverse transcriptase PCR (RT ‐ rPCR, mRNA target) and enzyme‐linked immunosorbent assay (ELISA; p57 antigen target) diagnostic accuracy for detection in Atlantic salmon broodstock from British Columbia, Canada, and assessed ELISA repeatability. In 2016, 4, 544 Atlantic salmon broodstock (no clinical signs of BKD or gross lesions) were sampled for ELISA testing of kidney tissue. Two groups of ELISA positives ( n  = 132) and two groups of a random sample of ELISA negatives ( n  = 137) were then tested with RT‐rPCR, and ELISA testing was repeated. ELISA testing of broodstock provided the best diagnostic sensitivity (DSe; less chance of false‐negative results). The use of joint RT‐rPCR and ELISA testing improved DSe over that from each test alone, if a sample was considered positive when either test result was positive. Using these testing schemes in combination with management practices can decrease the likelihood of vertical transmission from subclinically infected broodstock.